POLITIK HUKUM DALAM PEMBAHARUAN HUKUM PEMBERANTASAN TINDAK PIDANA KORUPSI - Putra, Adde Pramana; Ratnawati, Elfrida (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The global community is becoming more aware of corruption, which has fueled the expansion of the anti-corruption movement. Given that each country has a unique pattern of corruption-causing behavior, this anti-corruption movement seeks to eliminate corruption in each of these countries. Here, we finally understand what the Anti-Corruption Agency really is, or simply the Anti-Corruption Agency. The purpose of this research is to know and analyze the Criminal Law Reform in Corruption Crimes and to know and analyze the legal politics in the Criminal Law Reform in Corruption Crimes. This research is a normative legal investigation, which examines the laws and rules that exist or are used to deal with certain legal situations. Normative studies, also known as doctrinal research, are conducted on legal and regulatory documents and library items. Research in the library, especially secondary data examination. It is clear from the explanation above that the criminal act of office in the Criminal Code is the origin of corruption in Indonesia. Subsequent developments involving standards for proving criminal defamation occurred within criminal law as a distinct penal law. Regulations governing criminal acts of corruption outside the Criminal Code are developing rapidly. This arrangement is permitted according to Article 103 of the Criminal Code. The provisions of Chapters I-VIII of the text also apply to acts that are punishable by provisions of other laws, unless the law specifically stipulates otherwise, according to Article 103 of the Criminal Code.